(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The current research examines the quality of ground water in Kashmir (J&K), India, for human consumption and other purposes. For water quality testing, a total of six sampling sites in the research region were chosen. Pampore, Ganderbal, Batamaloo, Budgam, Sopore, and Sumbal are the sampling locations. Electrical conductivity, total dissolved solids (TDS), total suspended solids, chloride concentration, pH , sulphate content, and turbidity were used to evaluate water quality in the research region. The results of the sodium adsorption ratio (SAR) calculations along with the electrical conductivity suggested that the ground water in the study area can be used for irrigation without posing any risk to crop soils. The analytical data from the research region further reveals that, with the exception of a few spots, the ground water in the study area is appropriate for residential use.